Energy spectrum of transition metal impurity in a semiconductor with an ideal surface - Melnychuk, S.V.; Yurijchuk, I.M. (Condensed Matter Physics, 1999)
Energy spectrum of the transition metal impurity which substitutes a cation in a zink-blende structure semiconductor with an ideal surface is investigated theoretically. Model Hamiltonian of the semiconductor is treated by the semi-empirical tight-binding method, and energy of deep 3d-levels is determined by the Green function method within the framework of the Kikoin-Flerov model. Numerical calculations are performed for Cr impurity atoms in a CdTe semiconductor with an [100] ideal surface. It is shown that in the case when the impurity substitutes an atom near the surface, essential reconstruction of its energy spectrum takes place. One-electron t₂ - and e -levels occurring from 3d -volume states for the crystal with an ideal surface due to the lowering of the system symmetry split up. The magnitude of the splitting is rather small, when impurity is situated near but at some distance from the surface, and strongly increases when impurity substitutes an atom directly on an ideal surface. Main mechanisms of one-electron deep level formation in the forbidden gap of a semiconductor with ideal anion and cation surfaces are determined.